A Note on the Application of Article 234 of the Law of the Sea Convention in Light of Climate Change: Views from Russia. (3rd April 2017) - Dremliuga, Roman
ABSTRACT: This note explores the nature of Article 234 of the 1982 UN Convention on the Law of the Sea in light of decreasing Arctic ice cover. Despite various readings and possible interpretations of Article 234, the principal source of the rules of treaty interpretation is the 1969 Vienna Convention on the Law of Treaties. The note concludes, based on treaty interpretation, that there are no legal grounds for changing the Arctic regime based on Article 234 in light of the decreasing ice cover in the Arctic.